Neuropathic itch - Steinhoff, Martin; Schmelz, Martin (Pain, 2019)
AbstractNeuropathic itch is clinically important but has received much less attention as compared to neuropathic pain. In the past decade, itch-specific pathways have been characterized on a cellular and molecular level, but their exact role in the pathophysiology of neuropathic itch is still unclea